Associations Between Maternal Emotion Dysregulation, Infant Negative Affect, and Toddler Mental Health Depend on Newborn Neurobehavioral Profiles - Anna M. Zhou; Sarah E. Maylott; Anna M. Compton; Madeleine Bruce; Nicolette C. Molina; K. Lee Raby; Sheila E. Crowell; Elisabeth Conradt (Clinical Psychological Science, 2026)
We investigated maternal emotion dysregulation and profiles of newborn neurobehavior as predictors of infant temperamental negative affect and toddler psychopathology risk among 385 mother–infant dyads from birth to 18 months postpartum. Our findings show support for multiple mechanisms by which transdiagnostic risk develops in early childhood. For infants in the low-arousal, high-lethargy newborn neurobehavior profile, infant negative affect was a pathway by which maternal emotion dysregulation was associated with toddler socioemotional difficulties. In contrast, maternal emotion dysregulation was directly associated with toddler behavior dysregulation for infants in the high-arousal, high-stress neurobehavior profile at birth. Newborns in the high-attention, moderate-regulation neurobehavior profile were buffered against the effects of maternal emotion dysregulation on infant negative affect and toddler psychopathology risk. Our findings highlight the importance of examining the combination of newborn neurobehaviors with maternal mental health to understand the development of psychopathology risk in early childhood.